Adaptación de las empresas peruanas a los estándares internacionales en materia de compliance corporativo: análisis comparativo e implicancias legales - Salinas Rivas, Sergio (2023)
This article aims, from a panoramic viewpoint, to identify the main similarities and differences in the compared legislations in order to measure with greater certainty the legal and organizational implications for Peruvian companies to adapt their corporate compliance programs to the best practices and international standards in corporate compliance.